Penanaman Nilai Anti Korupsi di Kalangan Pelajar Sebagai Upaya Pencegahan Tindak Pidana Korupsi - Ahmad Muwafik; Jordan Fahran Brelian; Anggelica Regina Sinamora; Suhaidi Suhaidi; Mulyadi Mulyadi; Yuliana Yuli Wahyuningsih (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Currently, corruption is a very worrying problem. The rampant acts of corruption not only affect adults, but also students. Apart from curative action, in the form of providing sanctions, both criminal and administrative, to perpetrators of corruption. It is also important to take preventive action against acts of corruption. This preventive action is taken to prevent corruption in the future. Preventive measures can be taken for adults and students. Providing education on anti-corruption values among students is one of these preventive steps. Starting from this, the authors who are members of the Project Based Learning (PjBL) group organized anti-corruption values education for students at SMA Negeri 109 Jakarta. Through this education, the author also conducted research on the effectiveness of corruption education in terms of preventive measures for corruption. This research uses qualitative methods by collecting data through questionnaires and interviews. This research involved 80 respondents from students at SMA Negeri 109 Jakarta. The majority of respondents expressed the effectiveness of the education that the author held.